Adequate Tension and Clinical Results of Palmaris Longus Tendon Interpositional Graft in Closed Flexor Pollicis Longus Rupture - Lee, Joonha; Ku, Ki Hyeok; Lee, Jae Hoon; Baek, Jong Hun (Clinics in orthopedic surgery, 2025)
Volar plate fixation for distal radial fractures is the most common cause of closed rupture of the flexor pollicis longus tendon (FPL). For treating a closed FPL rupture, transferring the fourth flexor digitorum superficialis or a tendon graft from the palmaris longus (PL) can be performed. This study reports the results of tendon grafting using the PL in closed FPL rupture and discusses the provision of optimal tendon tension. This retrospective study included 11 out of 20 patients who underwent PL tendon graft for closed FPL rupture between 2013 and 2022, with a follow-up period of more than 12 months. There were 4 men and 7 women, with an average age of 62 years. The average period from the date of rupture to surgery was 39 days. Ruptures occurred due to volar plate fixation in 7 cases, ithout a specific cause in 2 cases, and after a steroid injection for trigger thumb in 2 cases. The rupture site was in zone 2 in 4 cases and zone 5 in 7 cases. The mean follow-up period was 59 months. Optimal tension for the grafted tendon was determined by comparing the intraoperative angles of the interphalangeal (IP) and metacarpophalangeal (MCP) joints with the angles of the same joints at the final follow-up. At the final follow-up, the mean IP joint motion was 61.0°, which was 81.5% of the contralateral side. The average range of motion of the MCP joint was 43.6°, which was 80.0% of the contralateral side. The pinch power was 90.8% of the contralateral side. Cases with > 70° IP joint motion were those in which the IP joint angle was > 45° during surgery. Moreover, the greater the flexion of the IP and MCP joints intraoperatively, the better the range of motion of the IP joints. Tendon grafting using the PL is recommended as an effective surgical method to achieve 81.5% of contralateral IP joint motion in cases of closed FPL tendon rupture. Over-tensioning of the tendon graft with IP Joint flexion more than 45° during surgery is recommended.